Analysis of Vaccenic and Elaidic acid in foods using a silver ion cartridge applied to GC × GC-TOFMS - Miyoung Yoo; Hyun Jeong Lee; Kwang-Won Lee; Dongwon Seo (Frontiers in Nutrition, 2024)
BackgroundTrans fatty acids (TFAs) are unsaturated fatty acids, with vaccenic acid (VA) and elaidic acid (EA) being the major constituents. While VA has been associated with beneficial effects on health and anti-cancer properties, EA is found in hardened vegetable oils and is linked to an increased risk of cardiovascular diseases. Therefore, this study aimed to develop a novel method for the quantitative measurement of VA and EA, aiming to accurately analyze individual TFA and apply it for the assessment of products containing TFAs.MethodsThe ratio of VA to EA (V/E ratio) was evaluated using a silver ion cartridge (SIC) solid phase extraction method removing cis-fatty acids (cis-FAs). Additionally, comparative analysis of the V/E ratio was conducted by the two methods (SIC treatment and untreated) using comprehensive two-dimensional gas chromatography combined with time-of-flight mass spectrometry (GC × GC-TOFMS).ResultsThe removal efficiency of cis-FAs was greater than 97.8%. However, the total TFA contents were not so different from SIC treatment. Moreover, this approach not only allowed for a more precise determination of the V/E ratio but also revealed a significant distinction between natural trans fatty acids (N-TFAs) and hydrogenated trans fatty acids (H-TFAs).ConclusionTherefore, the SIC coupled to the GC × GC-TOFMS presented in this study could be applied to discriminate N-TFA and H-TFA contents in dairy and fatty foods.